Proceedings of the 2003 ACM/SIGDA Eleventh International Symposium on Field Programmable Gate Arrays 2003
DOI: 10.1145/611817.611820
|View full text |Cite
|
Sign up to set email alerts
|

Architectures and algorithms for synthesizable embedded programmable logic cores

Abstract: As integrated circuits become more and more complex, the ability to make post-fabrication changes will become more and more attractive. This ability can be realized using programmable logic cores. Currently, such cores are available from vendors in the form of a "hard" layout. In this paper, we focus on an alternative approach: vendors supply a synthesizable version of their programmable logic core (a "soft" core) and the integrated circuit designer synthesizes the programmable logic fabric using standard cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…Without knowing the logic function that will eventually be implemented in the core, it is difficult to estimate the amount of programmable logic required. We designed two potential logic functions that might be implemented in the core, and measured the size of the core that would be required to implement each function (using custom-built CAD tools described in [9]). For our circuit, we found that a core consisting of forty-nine 3-LUTs would be sufficient for both potential logic functions; however, to allow some safety margin and anticipation of larger functions, a core consisting of sixty-four 3-input LUTs was used.…”
Section: A Programmable Logic Core Sizementioning
confidence: 99%
See 4 more Smart Citations
“…Without knowing the logic function that will eventually be implemented in the core, it is difficult to estimate the amount of programmable logic required. We designed two potential logic functions that might be implemented in the core, and measured the size of the core that would be required to implement each function (using custom-built CAD tools described in [9]). For our circuit, we found that a core consisting of forty-nine 3-LUTs would be sufficient for both potential logic functions; however, to allow some safety margin and anticipation of larger functions, a core consisting of sixty-four 3-input LUTs was used.…”
Section: A Programmable Logic Core Sizementioning
confidence: 99%
“…Unlike an embedded memory (which could also be used to provide a programmable implementation of the next state logic), the programmable logic core described in [9] is generous in the number of inputs. Furthermore, the size of the core increases only linearly as the number of inputs increases (as opposed to the exponential increase in the size of an embedded memory).…”
Section: B Connections Between the Core And The Fixed Logicmentioning
confidence: 99%
See 3 more Smart Citations